Four high performance nonproprietary concrete deck configurations for movable bridges. (1st August 2018) - Baghi, Hadi; Menkulasi, Fatmir; Montes, Carlos; Sandrock, Jean Paul; Gomez, Sergio
Highlights: Four high performance concrete deck configurations for movable bridges are presented. Each configuration weighs less than 0.96 kN/m 2 and features a unique concrete mixture. All deck configurations meet AASHTO's load demands. Two deck configurations meet AASHTO's deflection requirements. The failure mode is dominated by shear. Abstract: Four high performance nonproprietary concrete bridge deck configurations are presented for Louisiana's movable bridges as an alternative to traditional steel grid decks, which have exhibited durability problems. These concrete decks are as light and as deep as the traditional steel grid decks and meet the maximum weight limitation of 0.96 kN/m 2 imposed by the capacity of the mechanical systems that operate the movable bridges. The four concrete deck configurations feature unique nonproprietary concrete mixtures that possess high strength and low unit weight. The development of each concrete mixture is presented. All reinforcement is corrosion resistant and consists of glass fiber reinforced polymer (GFRP) bars and a two-way carbon fiber mesh. Several nonlinear finite element analyses are performed to simulate the behavior of all four concrete deck configurations from the onset of loading to failure and to ensure that the developed deck configurations meet AASHTO's load and deflections requirements. AASHTO's ultimate load demand is met regardless of whether the deck system is made continuous for live loads. Two deck configurations meet AASHTO's deflection requirements when continuity for live loads is established. The failure mode of the concrete deck panels is dominated by shear. The presented deck configurations offer the departments of transportation various feasible options and thus more flexibility for to how to address problems related to the deterioration of steel grid decks using locally available materials, and provide guidance as to what experimental testing to perform in the future.